2015
DOI: 10.1007/s11125-015-9361-2
|View full text |Cite
|
Sign up to set email alerts
|

After access: Divergent learning profiles in Vietnam and India

Abstract: In recent decades, both India and Vietnam have successfully expanded access to schooling to near-universal levels and have shifted their focus to quality-oriented policy reform. Yet, international and national evidence shows strongly contrasting learning profiles for children within the two systems. Simple indicators of numeracy suggest similar learning levels in both countries for 5-year-olds, but data suggest that, by the time they are 15, Vietnamese pupils outperform those in many OECD countries, while many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… Kaffenberger and Pritchett (2020) created adult retrospective learning profiles across ten countries using Financial Inclusion Insight data with young adults ages 18 to 37, as did Pritchett and Sandefur (2020) who used DHS literacy data from women aged 25–34 in 51 countries. The longitudinal study, Young Lives, utilizes similar questions across four countries – Ethiopia, India, Peru, and Vietnam – and has in several papers demonstrated vast differences in learning gains over time across countries using panel learning profiles ( Rolleston, 2014 ; Rolleston and James, 2015 ; Singh, 2020 ). Also using panel profiles, the LEAPS program in Punjab, Pakistan followed the same children over four rounds or years of schooling, highlighting learning changes as children transitioned from public to private school and vice versa ( Andrabi et al, 2008 ; Bau et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Kaffenberger and Pritchett (2020) created adult retrospective learning profiles across ten countries using Financial Inclusion Insight data with young adults ages 18 to 37, as did Pritchett and Sandefur (2020) who used DHS literacy data from women aged 25–34 in 51 countries. The longitudinal study, Young Lives, utilizes similar questions across four countries – Ethiopia, India, Peru, and Vietnam – and has in several papers demonstrated vast differences in learning gains over time across countries using panel learning profiles ( Rolleston, 2014 ; Rolleston and James, 2015 ; Singh, 2020 ). Also using panel profiles, the LEAPS program in Punjab, Pakistan followed the same children over four rounds or years of schooling, highlighting learning changes as children transitioned from public to private school and vice versa ( Andrabi et al, 2008 ; Bau et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-country context, several papers originating from Young Lives, a child-level panel data study utilizing similar questions from Ethiopia, India, Peru, and Vietnam, demonstrated vast differences in learning gains over time across countries using learning profiles (Rolleston, 2014;Rolleston and James, 2015;Singh, 2017). Others construct learning profiles from adult survey data.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the explanatory power of these 19 Ethiopian math teachers were tested on their mathematics knowledge in the primary school survey, but this test was very different from those given in the other three countries, and it did not assess their pedagogical skills. 20 For an earlier analysis of differences in student performance between Vietnam and India using the first three rounds of the Young Lives data, see Rolleston and James (2015).…”
Section: Discussionmentioning
confidence: 99%